2016
DOI: 10.1109/mcom.2016.1600397cm
|View full text |Cite
|
Sign up to set email alerts
|

RPL: The Routing Standard for the Internet of Things... Or Is It?

Abstract: Abstract-RPL, the IPv6 Routing Protocol for Low-Power and Lossy Networks, is considered the de facto routing protocol for the Internet of Things (IoT). Since its standardization, RPL contributed to the advancement of communications in the world of tiny, embedded, networking devices, by providing, along with other standards, a baseline architecture for IoT. Several years later, we analyze the extent to which RPL lived up to the expectations defined by the IETF requirements, and tie our analysis to current trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 14 publications
0
81
0
5
Order By: Relevance
“…Similarly to Langendoen et al, our system experienced random, difficult-to-debug watchdog reboots due to various reasons. Although routing protocols have advanced a lot, for example, in terms of standardization, the reliability of the modern 6LoWPAN / RPL network stack is still badly affected by the limited number of neighbor and routing table entries [13]. This paper once again raises the issue of the scarcity of easily available statistics and tha lack of visibilty of the network state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to Langendoen et al, our system experienced random, difficult-to-debug watchdog reboots due to various reasons. Although routing protocols have advanced a lot, for example, in terms of standardization, the reliability of the modern 6LoWPAN / RPL network stack is still badly affected by the limited number of neighbor and routing table entries [13]. This paper once again raises the issue of the scarcity of easily available statistics and tha lack of visibilty of the network state.…”
Section: Discussionmentioning
confidence: 99%
“…CC2650 has 20 kB RAM, which is not a large amount for a 32-bit system, taking into account the Contiki OS footprint and the large RAM requirements for network neighbor and routing tables [12]. Not having a neighbor or a routing table entry for an active neighbor can severely reduce the performance and stability of the network [13]; consequently, it is optimal to reserve as many entries as possible, aiming for an entry for each device in the network.…”
Section: B Memory Managementmentioning
confidence: 99%
“…For M2M communication the string mode of operation is therefore preferable because packets do not need to traverse the overall network up to the DODAG root, however, as reported in [1], the storing mode intrinsically introduces serious scalability issues, in particular for nodes close to the root, which must maintain potentially huge routing tables. Furthermore, in [1], it is also reported that point-to-point communications, i.e. M2M communications, suffer from poor reliability and such poor performance may prevent future adoption of RPL in the ever-increasing IoT applications scenario.…”
Section: B Rpl Routing Protocolmentioning
confidence: 99%
“…from sensor nodes to the sink, and point-to-multipoint, i.e. from the sink to sensor nodes [1]. Nowadays, instead, the application of WSN to industrial systems has introduced novel interaction pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The rank calculates from objective function. The objective function provides the optimal solution for select the best parent and sends the data towards the root [9][10].…”
Section: Rplmentioning
confidence: 99%